Students with ADHD: Social Skills, Behavioral Problems, Academic Performance, and Family Resources - Abrahão,Anaísa Leal Barbosa (2021)
Abstract ADHD constitutes a developmental risk. The general aim was to identify social skills, behavior problems, academic performance and family resources of children with ADHD, with the specific aim being to compare students regarding indicators of ADHD and the use or not of medication. Participants were 43 Elementary Education I students (M=9.6 years, SD=1.5), 43 parents (M=39.1 years, SD=7.6) and 38 teachers (M=43.1 years, SD=8.4). The instruments used were the Inventory of Social Skills, Behavior Problems and Academic Competence (SSRS-BR), Conners’ Scale and the Inventory of Family Resources. The collection was carried out in public schools. The results showed that the students had scores higher than the reference sample in Behavior Problems and Social Skills and lower in classes of social skills and Academic Competence; the presence of family resources; and grades above 5.0 as a school mean. We concluded that there is a need for interventions with the studied population.